The Impact of Personality Traits on Perceived Investment Performance: The Moderating Role of Social Interaction - Ninditya Nareswari; Citra Wanodya Rahmani; Nugroho Priyo Negoro (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2021)
Each investor has an investment plan to reach their investment objectives. Perceived investment performance was affected by a high level of the psychological aspect.  The purpose of this study was to test the effect of the Big Five personality traits on the perception of investment performance. This study also tests the moderating role of social interaction. PLS-SEM was used to test the hypotheses. Used individual stock investors in Indonesia, the findings showed that openness personality had a negative effect on perceived investment performance. Otherwise, conscientiousness, extraversion, agreeableness, and neuroticism had a positive impact on perceived investment performance. The results also show that social interaction moderates the relationship between conscientiousness, agreeableness, and perceived investment performance. This result shows that information selection and investment knowledge is important when allocating asset to achieve investment objectives.